2016
DOI: 10.1016/j.jneb.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Education Resources in North Carolina–Based Head Start Preschool Programs: Administrator and Teacher Perceptions of Availability and Use

Abstract: Creative strategies for addressing NE resource availability and use and barriers (eg, NE integration with educational standards) in Head Start are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…Schools are important places to deliver policies, acts, or interventions [18]. Studies have reported that the lack of understanding about the importance of nutrition education in school administrators was a significant barrier to deliver nutrition education [26,38], which is consistent with our findings. In our study, more than 31.3% of the teachers who never taught nutrition courses claimed that teaching nutrition was not required by school administrators.…”
Section: Current Status and Barriers Of Delivering Nutrition Educatiosupporting
confidence: 91%
“…Schools are important places to deliver policies, acts, or interventions [18]. Studies have reported that the lack of understanding about the importance of nutrition education in school administrators was a significant barrier to deliver nutrition education [26,38], which is consistent with our findings. In our study, more than 31.3% of the teachers who never taught nutrition courses claimed that teaching nutrition was not required by school administrators.…”
Section: Current Status and Barriers Of Delivering Nutrition Educatiosupporting
confidence: 91%
“…While research-based evidence supports the benefits of implementing gardening in classrooms for young children, teachers and administrators reported the barriers that prevent the implementation of traditional gardening into schools were time, funding, administrative support, space, limited technology, and lack of teacher training [10][11][12][13]31]. Many of these barriers can be addressed by additional resources and effective implementation.…”
Section: Addressing Barriers To School Gardeningmentioning
confidence: 99%
“…School gardening can encourage students to consume more fruits and vegetables and improve their experiences with healthy food habits [8,9]. However, the time necessary to integrate gardening into curricula, space needed to effectively plant, and lack of training inhibit many teachers from incorporating gardening into their classrooms [10][11][12][13]. Therefore, a two-tier approach to build capacity for sustaining nutrition education programs inclusive of gardening education is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini ditunjukan pula pada penelitian ini, yaitu pada analisis kuisoner pengukuran keterampilan yang menunjukkan bahwa keterampilan guru dalam memberi edukasi mengenai "dampak negatif bagi kesehatan apabila siswa jajan di sembarang tempat" naik setelah intervensi. Strategi pendidikan kesehatan tentang makanan sehat perlu dikolaborasikan dengan guru (Lisson, et al, 2016). Model KOGUSIGA menjadikan guru sebagai salah satu pemeran utama dalam memberikan pendidikan gizi sebagai usaha meningkatkan pemenuhan gizi siswa yang seimbang.…”
Section: Hasilunclassified